Effect of Surface Functionalization of Si3N4 Fillers on Thermal and Mechanical Properties of TIMs - Zaifu Jin; JinHong Li; Jiaqing Zhao; Yixuan Ge (Advanced Materials Interfaces)
Abstract Thermal interface materials (TIMs), which consist of polymers and thermally conductive fillers, are crucial for improving heat dissipation. This study examines the impact of surface functionalization of Si₃N₄ thermal conductive fillers on the performance of TIMs. Si₃N₄ fillers are modified with silane coupling agents of varying alkyl chain lengths, producing fillers with contact angles ranging from 25° to 151.2°, thereby ensuring enhanced interfacial compatibility with various polymers. The modified fillers are incorporated into three common polymers—silica gel (SG), epoxy resin (EP), and polyurethane (PU)—to fabricate TIMs. When the contact angle of Si₃N₄ fillers is 73.3°, they demonstrate excellent interfacial compatibility with EP, leading to a 54.37% increase in thermal conductivity and a 162.75% enhancement in elongation at break for the TIM. At a contact angle of 132.7°, the TIMs prepared with SG exhibit an 86.36% increase in thermal conductivity and a 23.88% increase in elongation at break. Given that the original Si₃N₄ already possesses adequate interfacial compatibility with PU, no further modification is required. These findings offer valuable insights for future research aimed at optimizing Si₃N₄ fillers and TIMs to achieve enhanced thermal and mechanical properties.